Lytic and genomic properties of spontaneous host-range Kayvirus mutants prove their suitability for upgrading phage therapeutics against staphylococci - Botka, Tibor; Pantůček, Roman; Mašlaňová, Ivana; Benešík, Martin; Petráš, Petr; Růžičková, Vladislava; Havlíčková, Pavla; Varga, Marian; Žemličková, Helena; Koláčková, Ivana; Florianová, Martina; Jakubů, Vladislav; et al. (Scientific reports, 2019)
Lytic bacteriophages are valuable therapeutic agents against bacterial infections. There is continual effort to obtain new phages to increase the effectivity of phage preparations against emerging phage-resistant strains. Here we described the genomic diversity of spontaneous host-range mutants of kayvirus 812. Five mutant phages were isolated as rare plaques on phage-resistant Staphylococcus aureus strains. The host range of phage 812-derived mutants was 42% higher than the wild type, determined on a set of 186 methicillin-resistant S. aureus strains representing the globally circulating human and livestock-associated clones. Comparative genomics revealed that single-nucleotide polymorphisms from the parental phage 812 population were fixed in next-step mutants, mostly in genes for tail and baseplate components, and the acquired point mutations led to diverse receptor binding proteins in the phage mutants. Numerous genome changes associated with rearrangements between direct repeat motifs or intron loss were found. Alterations occurred in host-takeover and terminal genomic regions or the endolysin gene of mutants that exhibited the highest lytic activity, which implied various mechanisms of overcoming bacterial resistance. The genomic data revealed that Kayvirus spontaneous mutants are free from undesirable genes and their lytic properties proved their suitability for rapidly updating phage therapeutics.
Keywords: zastoupení bazí; Genome Size; mutace; délka genomu; Staphylococcus aureus; Genome, Viral; bakteriofágy; Drug Resistance, Bacterial; jednonukleotidový polymorfismus; Genomics; Polymorphism, Single Nucleotide; Methicillin; bakteriální léková rezistence; Base Composition; genom virový; Mutation; genomika; Bacteriophages; methicilin